Análisis de la distribución espacial y temporal de los defectos congénitos registrados entre 2004 y 2008 en un hospital de tercer nivel en Cali, Colombia (2011)
Objective: To describe the spatial and temporal distribution of major birth defects and to identify clusters at spatial, temporal and space-temporal levels. Methods: A descriptive study was developed about the space and time distribution of defects registered in Cali between March 2004 and October 2008 using principles of spatial statistics, namely the spatial data exploratory analysis. Results: Higher case density and prevalence was observed among neighborhoods of eastern Cali. Three districts («communes») of the 21 in the city showed a larger probability (50 to 100% larger) of major birth defects. Significant clusters (p<0.05) were proven in spatial, temporal and space-temporal analysis. Conclusions: Birth defects were confirmed clustered in several communes at the poorest areas of the city. Occurrence of defects in this area may be associated, at least in part, to social and environmental inequities. © 2011 Universidad del Valle, Facultad de Salud.